1995
DOI: 10.1007/bf02537030
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of gonadotropin‐stimulated ovarian steroid production by polyunsaturated fatty acids in teleost fish

Abstract: The effects of the polyunsaturated fatty acids (PUFAs)--eicosapentaenoic acid (EPA), docosahexaenoic acid (DHA), and arachidonic acid (AA)--on in vitro steroid production by full-grown prematurational ovarian follicles from goldfish and rainbow trout were investigated. EPA and DHA inhibited gonadotropin-stimulated testosterone production in a dose-related manner, but AA was inhibitory only at the highest dose tested (400 microM). AA alone stimulated testosterone production by increasing cAMP production, but th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
44
0
1

Year Published

1996
1996
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(52 citation statements)
references
References 53 publications
4
44
0
1
Order By: Relevance
“…Other derivatives of PI, diacylglycerol and inositol phosphates, can also serve as intracellular messengers. In recent years, substantial progress has been made in the understanding of these and other regulatory functions mediated by fatty acids in fish, and they are not discussed further here (Tocher et al, 1991;Van Der Kraak and Wade, 1994;Mercure and Van der Kraak, 1995;review, Sargent, 1995).…”
Section: Summary and Biological Significancementioning
confidence: 99%
“…Other derivatives of PI, diacylglycerol and inositol phosphates, can also serve as intracellular messengers. In recent years, substantial progress has been made in the understanding of these and other regulatory functions mediated by fatty acids in fish, and they are not discussed further here (Tocher et al, 1991;Van Der Kraak and Wade, 1994;Mercure and Van der Kraak, 1995;review, Sargent, 1995).…”
Section: Summary and Biological Significancementioning
confidence: 99%
“…Additionally, fatty acids are metabolized differently during the reproductive cycle: while some are catabolized for energy, others are stored in the gonad for structural purposes, such as membrane formation or eicosanoid synthesis (Mazorra et al, 2003;Jerez et al, 2016). For example, arachidonic acid (ARA, 20:4 n-6) is one of the major nutrients to ensure reproductive success in many fish species (Tocher, 2010), as is the main precursor for the 2-series prostaglandins (PG-2), eicosanoids that stimulate steroid synthesis in the ovary, trigger oocyte maturation and affect the sexual behavior of females (Mercure & Van der Kraak, 1995;Tocher, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Teleost gonads are particularly rich in DHA and EPA (Sargent et al 2002, Bobe andLabbé 2010). Specifically, spermatozoa membrane contain extremely high levels of DHA (Labbe et al 1995;Asturiano et al 2001;Bobe and Labbé 2010) Thus, these fatty acids derived directly from the dietary input of broodstock as well as from body reserves are crucial to gonadogenesis in both male and female and also to fecundity and to embryo and early larval development (Wade et al 1994;Mercure and Van Der Kraak 1995;Asturiano et al 2001). Previous studies conducted by our research group have shown that both ovary and testicle of gilthead seabream exhibited a dramatic increase in DHA and EPA contents before the beginning of spawning, being it partly due to mobilization from the liver and muscle (Almansa et al 2001;Martín et al 2009).…”
Section: Introductionmentioning
confidence: 97%